PENGARUH PERSEPSI MANFAAT, TARIF DAN KEPERCAYAAN TERHADAP KEPUTUSAN PENGGUNAAN PRODUK E-MONEY (STUDI KASUS PADA PENGGUNA LAYANAN GO-PAY DI KOTA JAKARTA) - Muhammad Adi Wibowo; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2019)
The growth of non-cash transactions is still less than optimal in Indonesia, especially, when it sees from low number of public awareness and from e-money products distribution that are still concentrated in Jakarta. In Jakarta itself, there are many choices of e-money service products and it is known that the most widely used e-money product is Go-Pay. The problem in this study is that Go-Pay as the most widely used product of e-money services apparently still has many problems and still has high number of complaints from 2016 - 2017. The purpose of this study is to determine the effect of perceived of usefulness, fare and trust on  decision to use e-money service products Go-Pay in Jakarta. This type of research is explanatory research, with total of sample is 100 respondents with a sampling technique using non-probability sampling with an accidental sampling approach. The analytical method uses validity test, reliability test, classic assumption test, correlation coefficient, determination coefficient, simple linear regression analysis, multiple linear regression analysis, and significance test (t test and f test) using the SPSS version 16.0 application. Perceived of usefulness variable is in the high category. The value of t count (4.106) > t table (1.984). The correlation coefficient is 0.383 and the coefficient of determination is 14.7%. Fare variable is in the high category. The value of t count (4,348) > t table (1,984). The correlation coefficient is 0.402 and the determination coefficient is 16.2%. Trust variable is in the high category. The value of t count (4.486) > t table (1.984). The correlation coefficient is 0.413 and the determination coefficient is 17.0%. Decision to use variable is in the high category. The value of f count  (17,617) > f table (2,70).Conclusion of this study is perceived of usefulness, fare and trust are equally influential on decision to use. It states that if perceived of usefulness is high, and fare is high, and trust is high. it will make a higher result for decision to use. This can be seen in this study that users of the Go-Pay service, variable perceived of usefulness, fare and trust together have a strong influence on decision to use.